2010
DOI: 10.26719/2010.16.7.752
|View full text |Cite
|
Sign up to set email alerts
|

Domestic abuse before, during and after pregnancy in Jahrom, Islamic Republic of Iran

Abstract: We conducted a cross-sectional study among 300 women with a child aged 6 to 18 months, to determine the prevalence and determinants of domestic abuse against women in Jahrom; before, during and after pregnancy. The prevalence of abuse during pregnancy (42%) was lower than during the 1 year before pregnancy (51.7%) and after delivery (53.5%). The overall prevalence of emotional abuse, sexual abuse and physical abuse was 53.5%, 34.7% and 26.7% respectively. Abuse during any previous period was a strong risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 9 publications
6
16
0
Order By: Relevance
“…In Asia, the highest percentage was observed in the Islamic Republic of Iran where there was a prevalence of intimate partner violence during pregnancy of 42.0% (that increases to 52.5% after pregnancy), in a hospital study conducted with 300 married women (35). The lowest prevalence was found in China, where 4.3% during the approximate 9 months of pregnancy was detected in a study of 12,440 women from 32 communities (36).…”
Section: An Approach Around Prevalence Data For Ipv During Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…In Asia, the highest percentage was observed in the Islamic Republic of Iran where there was a prevalence of intimate partner violence during pregnancy of 42.0% (that increases to 52.5% after pregnancy), in a hospital study conducted with 300 married women (35). The lowest prevalence was found in China, where 4.3% during the approximate 9 months of pregnancy was detected in a study of 12,440 women from 32 communities (36).…”
Section: An Approach Around Prevalence Data For Ipv During Pregnancymentioning
confidence: 99%
“…According to studies conducted in a variety of countries with diverse social and cultural contexts, discrepancies between violence before, during and after pregnancy are evident. Intimate partner violence commonly decreases with pregnancy (23,(35)(36)40). In Mexico, however, pregnancy does not appear to be a protective factor against couple violence (41).…”
Section: Patterns Of Intimate Partner Violence In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors also found that most women who report PIPV during pregnancy state that PIPV also occurred before and after pregnancy 40,41 . In summary, PIPV tends to recur [38][39][40][41] , so the possibility of temporal bias in this study seems small. Given these considerations, the study findings indicate the impact of PIPV on LBW, especially the role of PIPV severity on its occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Although short, this period includes the month after birth, that is, it is possible that the outcome preceded exposure, which would be a temporal bias. Nonetheless, PIPV seems to be chronic 38,39 . Gartland et al 38 found that few women report the first act of violence after delivery, suggesting that PIPV may have begun before delivery.…”
Section: Discussionmentioning
confidence: 99%